A CRMP4-dependent retrograde axon-to-soma death signal in amyotrophic lateral sclerosis - Maimon, Roy; Ankol, Lior; Gradus Pery, Tal; Altman, Topaz; Ionescu, Ariel; Weissova, Romana; Ostrovsky, Michael; Tank, Elizabeth; Alexandra, Gayster; Shelestovich, Natalia; Opatowsky, Yarden; Dori, Amir; et al. (The EMBO journal, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal non-cell-autonomous neurodegenerative disease characterized by the loss of motor neurons (MNs). Mutations in CRMP4 are associated with ALS in patients, and elevated levels of CRMP4 are suggested to affect MN health in the SOD1G93A -ALS mouse model. However, the mechanism by which CRMP4 mediates toxicity in ALS MNs is poorly understood. Here, by using tissue from human patients with sporadic ALS, MNs derived from C9orf72-mutant patients, and the SOD1G93A -ALS mouse model, we demonstrate that subcellular changes in CRMP4 levels promote MN loss in ALS. First, we show that while expression of CRMP4 protein is increased in cell bodies of ALS-affected MN, CRMP4 levels are decreased in the distal axons. Cellular mislocalization of CRMP4 is caused by increased interaction with the retrograde motor protein, dynein, which mediates CRMP4 transport from distal axons to the soma and thereby promotes MN loss. Blocking the CRMP4-dynein interaction reduces MN loss in human-derived MNs (C9orf72) and in ALS model mice. Thus, we demonstrate a novel CRMP4-dependent retrograde death signal that underlies MN loss in ALS.
Keywords: amyotrofická laterální skleróza; signální transdukce; Signal Transduction; proteiny nervové tkáně; axonal transport; superoxiddismutasa 1; CRMP4; Nerve Tissue Proteins; retrograde signaling; axony; Motor Neurons; Axonal Transport; buněčná smrt; zvířata; myši; Cells, Cultured; Dyneins; myši inbrední C57BL; Mice; buněčné linie; dynein; Cell Line; ALS; kultivované buňky; Mice, Inbred C57BL; Amyotrophic Lateral Sclerosis; Axons; motorické neurony; Animals; dyneiny; Cell Death; axonální transport; Superoxide Dismutase-1